Assessing India's Rise and the Road Ahead. Issue 5 (2nd September 2016) - Bergenwall, Samuel
Abstract: This article analyses India's economic, military and political rise in the international state system. It concludes that India is on the rise in all three power dimensions, underpinned by a larger share of global GDP. However, it also identifies the constraints on the way. On matters concerning its economy, India lags behind in industrial prowess, innovation, socio-economic development and financial strength. While modernising its defence capabilities, it faces obstacles due to budget issues, institutional constraints and a weak defence industry. At the global level, its political leverage is circumscribed by its small diplomatic corps, limited foreign aid, underutilised soft power assets and by an immediate neighbourhood that consumes much of its political energy. India's rise could also be delayed by various domestic constraints as well as failure to adapt to 'the second machine age' and 'the return of geopolitics'. Nevertheless, the probabilities of India's continued rise in the international system are good, given its favourable demographics and catch-up opportunities related to labour productivity, urbanisation and digitisation.